Determinação experimental do coeficiente de reaeração, em rios e canais abertos, com o emprego de traçadores - Vendrame, Iria Fernandes (1982)
In this work, the reaeration coefficient, K2 in natural waters is determined experimentally using Tsivoglou's radioactive tracer method. The technique employed involves the use of an inert radioactive gas, Kr-85, as a tracer for oxygen, tritiated water, HTO, to correct for dispersion and dilution of tracer, and a fluorescent tracer, Amidorodamina G.E., with a view to determining the instant at which to start sample collection in field work. The experiments were performed in a part of the Mato Grosso channel and Saracuruna river (RJ) along a 11.2 km reach. A summary of reaeration modelling studies, a comparative analysis of the experimental methods for the determination of the reaeration coefficient, and radioactive tracer method fundamentals, are presented along with specific experimental details and special devices which were used in both laboratory and field work. Measured values of K2 are compared with computed values obtained from predictive models and are fit to a semiempirical equation involving hidraulic parameters. An analysis is made of losses of Amidorodamina G. E., and these are compared with those of conservative tracer, HTO.